AKTUALISASI DIRI TOKOH YURI DALAM KOMIK BARA NO TAME NI KARYA AKEMI YOSHIMURA TINJAUAN PSIKOLOGI SASTRA - Ayu Utari Kusumadewi, Anak Agung (Humanis; Volume 1. No. 2. Desember 2012)
Psychological analysis of literature is a way to know about human psychological state from the characters in literary works. Bara no tame ni is the biggest work from Akemi Yoshimura, a Japanese comicus. It received a Shogakukan Manga Award in 1993. It is a story about an ugly fatty eighteen years old girl named Yuri Makurano who trying her best to make her dream comes true. Her actions depend on her psychological state and that makes her experienced something important called self actualization. Self actualization is the intrinsic growth of what is already in the organism, or more accurately, of what the organism is. Abraham Maslow’s hierarchy of needs indicates that a human must fulfill his basic needs before he going to fulfill his self actualization need.
Keywords: psychological literature, hierarchy of needs, self actualization 1. Latar